2006
DOI: 10.1507/endocrj.k05-182
|View full text |Cite
|
Sign up to set email alerts
|

A Family Showing Resistance to Thyroid Hormone Associated with Chronic Thyroiditis and its Clinical Features: A Case Report

Abstract: Abstract. Resistance to thyroid hormone (RTH) is characterized by decreased tissue responsiveness to thyroid hormone, due mainly to mutation of the thyroid hormone receptor (TR) β gene. It has been reported that serum of patients with RTH lacks autoantibodies against thyroglobulin (Tg) and thyroid peroxidase (TPO), except in rare cases where there is cooccurrence of coincidental autoimmune thyroiditis. Here we describe the five-year medical history of a Japanese woman and her father with RTH and coincidental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Further, a similar adult case in which a P453T mutant TR was associated with Hashimoto disease and hypothyroidism has been reported, the serum TSH level being 140 mU/mL with 0.34 ng/dL (normal, 0.75-1.75) serum FT4 (16). In this case, replacement therapy with 100 mg/day of levothyroxine improved the symptoms of hypothyridism, suggesting that her hypothyroidism was not severe.…”
supporting
confidence: 68%
“…Further, a similar adult case in which a P453T mutant TR was associated with Hashimoto disease and hypothyroidism has been reported, the serum TSH level being 140 mU/mL with 0.34 ng/dL (normal, 0.75-1.75) serum FT4 (16). In this case, replacement therapy with 100 mg/day of levothyroxine improved the symptoms of hypothyridism, suggesting that her hypothyroidism was not severe.…”
supporting
confidence: 68%
“…Concomitant autoimmune thyroiditis in patients with RTH is rarely reported [9, 21, 22]. As our patient was positive for anti-TPO antibodies, we diagnosed her as having RTH with coincidental autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 64%
“…Sato and cols. (6) reported that RTH is not associated with the presence of antithyroid antibodies except in rare cases in which autoimmune thyroiditis coexists. Gavin and cols.…”
Section: Discussionmentioning
confidence: 99%
“…Sato and cols. (6) reported that patients with RTH in general have no antithyroglobulin or antithyroperoxidase antibodies, excepting rare cases in which there is coexistence of chronic autoimmune thyroiditis.…”
Section: Introductionmentioning
confidence: 99%